Pengaruh Penggunaan Tepung Biji Durian (Durio Zibethinus Murr) Dalam Ransum Terhadap Performans Produksi Ayam Broiler - Tunggul Ferry Sitorus (MOUSE JURNAL HUMANIORA, 2025)
This study aims to determine the effect of using durian seed flour on the performance of broiler chickens aged 8-35 days. This research was conducted in the experimental field of the Faculty of Animal Husbandry, University of HKBP Nommensen Medan in Simalingkar A Village, Pancur Baru District, Deli Serdang Regency for 35 days. This study used 100 broiler chickens strain CP 707. The research method used was an experimental method with a Completely Randomized Design (CRD) consisting of 5 ration treatments and 4 replications, namely P0 (0% durian seed flour in the ration), P1 (5% durian seed flour in the ration), P2 (10% durian seed flour in the ration), P3 (15% durian seed flour in the ration) and P4 (20% durian seed flour in the ration). The data obtained in this study were analyzed for variance (ANOVA) and then continued with the Honest Significant Difference test. The conclusion obtained from the results of the study showed that the administration of durian seed flour in broiler chicken rations had no significant effect (P>0.05) on ration consumption and very significant effect (P<0.01) on body weight gain and ration conversion of aged broiler chickens 8-35 days. Provision of durian seed flour in the ration should be given as much as 5%.